FAKTOR-FAKTOR YANG MEMPENGARUHI KELENGKAPAN PEMBERIAN IMUNISASI DASAR PADA BAYI DAN BALITA DI POSYANDU DESA PANDAWANGI TEMPEH LUMAJANG - Soleha, Lailatul Badriatus; Maulina, Rifzul; Sulistiyah, Sulistiyah (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Immunization is one of the most effective health interventions in an effortto reduce the mortality rate of infants and toddlers. Pandanwangi Village The problem in this research are mother’s age, maternal education level, the support from family of immunization with complete primary immunization in infants. This type of research is observational analytic with a cross sectional approach. The population in this study are mothers who have children that reached the age of 9-12 months in the Pandanwangi village. The ratio 1:1 for case and control groups, then a large sample study of 30 are obtained cases and 30 controls. The sample selection technique uses propotional area probability random sampling. The instrument is form of questionnaires. From the result showed that the variables related to the completeness of immunization are the maternal education level (p value = 0,008, OR = 4,297), maternal knowledge level (p value = 0,004, OR = 4,750), maternal employment status (p value = 0,0001, OR = 7,667), and support of family members on immunization (p value = 0,003, OR = 5,714). Based on the research results, suggestions which may be presented for health workers is to provide information to mother and families about the importance of basic immunization and monitoring the completeness of immunization is needed and for the mothers who have babies should take the time to immunizing children.